2016
DOI: 10.1136/tobaccocontrol-2015-052805
|View full text |Cite
|
Sign up to set email alerts
|

Recall, appeal and willingness to try cigarettes with flavour capsules: assessing the impact of a tobacco product innovation among early adolescents

Abstract: Background Use of flavour capsule varieties (FCVs) of cigarettes has rapidly increased in many countries. Adolescents are attracted to flavours; yet, surprisingly, no quantitative study has explored adolescents’ perceptions of these products. Objective To characterise the appeal of FCVs for young adolescents in Mexico. Methods In 2015, surveys were conducted with a representative sample of Mexican middle school students (n=10 124; ages 11–16 years; mean 12.4 years). Students viewed and rated packs for FCVs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 35 publications
3
54
0
7
Order By: Relevance
“…[15][16][17][18] Los datos utilizados en el estudio permiten que el efecto de la exposición a la publicidad en favor del tabaco sea evaluado más que nada a partir de las percepciones reales de los adolescentes y no de la consideración de las prohibiciones formales vigentes. Como es posible que se apliquen algunas prohibiciones sin que sean respetadas, esta metodología permite captar asociaciones que pueden estar presentes incluso en presencia de prohibiciones oficiales.…”
Section: Discussionunclassified
“…[15][16][17][18] Los datos utilizados en el estudio permiten que el efecto de la exposición a la publicidad en favor del tabaco sea evaluado más que nada a partir de las percepciones reales de los adolescentes y no de la consideración de las prohibiciones formales vigentes. Como es posible que se apliquen algunas prohibiciones sin que sean respetadas, esta metodología permite captar asociaciones que pueden estar presentes incluso en presencia de prohibiciones oficiales.…”
Section: Discussionunclassified
“…17 It is also consistent with research in the US, with young adult menthol smokers suggesting that capsule cigarettes would attract beginners, 10 and research in Mexico, with adolescents found to be more interested in trying cigarettes with capsules than without them. 9 With innovation fundamental to value growth for tobacco companies and younger people most receptive to such innovation, 18 the capsule segment has been a welcome success story for tobacco companies.…”
Section: Yum That Is Not Going To Help Me Quit (16-17 Female C2de)mentioning
confidence: 99%
“…5 Surprisingly few studies have explored use of these products. [7][8][9][10] In the Australian School Students Alcohol and Drug Survey with 12-17 year olds, more than half (51.8%) of past-month smokers reported having used capsule cigarettes, more likely females than males. Past-month smokers were more likely to report having used them six or more times (22.5%) rather than two-five times (17.2%) or just once (12.1%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abad-Vivero et al assess the impact of flavour capsules, a cigarette product innovation 6. In surveys with Mexican middle school students, flavour capsule variants of established brands were recalled and perceived as attractive, increasing interest in trying the products.…”
mentioning
confidence: 99%